DYEING OF SILK FABRIC WITH EXTRACT FROM CAESALPINIA SAPPAN - Taif, Basitah; Tajuddin, Rosita Mohd; Som, Siti Hernida Mohd (PEOPLE: International Journal of Social Sciences, 2019)
Dye extract derived from Caesalpinia sappan bark has been studied for incoherent colour saturation and poor fastness properties by local textile craftsman in Malaysia. This research was carried out to investigate the intensity of colour absorbed by silk fibre and its fastness properties against light. Boiling method was applied to extract its natural colourant; and mordanting and dyeing were conducted through pre-mordanting, simultaneous mordanting and post-mordanting procedures. Visual observations were made to examine the shades of dyed samples and the lightfastness properties were analysed via grey scale method. The dye ability results showed that all fabric samples appeared in different range of shades where the darkest colour of Post-mordanting was discovered almost similar to the control sample. It is concluded that natural dye extracted from the Caesalpinia sappan bark produced variation of shades on silk fabrics and the range of fading indicates resemblance between treated and untreated fabric.